Who’s Who in Maine Aquaculture? Understanding the Landscape of Aquaculture Actors and Priorities - Cleaver, Caitlin; Fail, Robin; Miller, Molly; Farr, Emily; Batchelder, Jessica; McMahan, Marissa; Staab, Maeve (Maine Policy Review, 2023)
The Maine aquaculture sector has been rapidly evolving in the last 15 years and is looked to as an area of economic development potential for the state. While there are many actors engaged in aquaculture development, there is less clarity around whose priorities are shaping the direction of the sector, how those priorities have evolved over time, and who benefits. Our paper seeks to answer the following question: Who has shaped aquaculture development priorities in Maine, and how? Through the analysis of organizational priorities, written testimony, and grant funding information, we will document the role of different actors and summarize the types of research and development funded. Our analysis and collective experience working with the aquaculture sector offers insight into whose priorities are included as aquaculture is developed, whose are excluded, and the implications for equity and inclusion in the Maine aquaculture sector.